The Purpose, Benefits, and Wisdom of Death from the Perspective of Tafsir Al-Qur'an Al-'Azim - Tammulis; M, M.Galib; Abubakar, Achmad; Mahfudz, Muhsin (PT FORMOSA CENDEKIA GLOBAL, 2024)
The purpose of this study is to reveal the purpose, benefits, and wisdom of death from the perspective of tafsir al-qur'an al-'azim. This type of research is a descriptive qualitative research. In this study, the author uses the maudu'i method. because the object of study in this study focuses on one particular theme, namely about al-maut. The results showed that; 1). The purpose of death in Tafsir al-Qur'an al-'Azim is to test who is the best in his deeds while living in this world; to get a reward for his deeds; to enforce justice and is proof of the power of Allah swt. 2). The benefits and wisdom of death in Tafsir al-Qur'an al-'Azim are: First, death as a mercy for believers. Second, death as advice or warning for believers to do good deeds and repent. Third, the existence of death will be an entertainment for believers in facing the life of the world, as well as instill a sense of love for the hereafter. Fourth, it inspires to dare to defend the truth and jihad for the sake of Allah.